The Urgency of Islamic Education Management in Era Globalization - Ahmed, Anjum; Abidin, Zaenal; Mahfooz, Ahmed (Zabags International Journal of Education, 2023)
This research aims to conduct research by applying descriptive analysis techniques using library research. Testing the validity of the data was carried out by triangulating the data from references, both in terms of method and in terms of sources. the data or materials needed to complete the research come from the library, either in the form of books, encyclopedias, dictionaries, journals, documents, magazines, and so on, Data analysis in this study is content analysis. The results of this research indicate that Islamic education management, as a branch of management, is very important an important function for critics, intellectuals and the people of this nation to be a good and moral learner and educator. The role of educators in criticizing globalization is very important. Moreover, in the management of Islamic education it must be pay attention to, and be critical of, global competition. Because, the (bad) influence of globalization can quickly enter our lives, into our subconscious, to act as desired by the development of globalization.